PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP MOTIVASI BELAJAR MAHASISWA PENDIDIKAN BIOLOGI DI UNIVERSITAS PENDIDIKAN MUHAMMADIYAH SORONG - Ribut Wahyu Eriyanti; Atok Miftachul Hudha; Edi Sutomo (Bio-Lectura : Jurnal Pendidikan Biologi, 2023)
This research was conducted to determine the use of the Project Based Learning (PJBL) learning model on the motivation of biology education students at the Muhammadiya Sorong Education University. This research was carried out in semester 4 in classes 4.1 and 4.2 at the Muhammadiyah University of Education, Sorong, academic year 2022/2023. The research design used was Quasi Experiment Pretest Posttest Control Group Design. In Quasi Experiment Pretest Posttest Control Group Design, the experimental and control groups are selected randomly. Data collection was carried out through pretest, posttest and observation sheets. Based on the results of research in the control class, the average overall score of the control class motivation indicators was 2.35, including in the medium category with a percentage of 57.47%. Meanwhile, in the experimental class there was a significant difference between the class given conventional learning and the class given Project Based Learning (PJBL). Student motivation appears to have increased. The questionnaire value of 2.51 is included in the high category with a percentage of 60.13%. Thus, learning with the Project Based Learning (PJBL) model can be said to increase the learning motivation of 4th semester students in the Biology Education Department at the Muhammadiyah Sorong University of Education.